2017
DOI: 10.1292/jvms.16-0630
|View full text |Cite
|
Sign up to set email alerts
|

Comparative serological investigation between cat and tiger blood for transfusion

Abstract: Evidence suggests that non-domesticated felids inherited the same AB-erythrocyte antigens as domestic cats. To study the possible compatibility of tiger blood with that of other endangered felidae, blood samples from captive tigers and domestic cats were subjected to an in vitro study. The objectives of this study were to (1) identify whether the captive tigers had blood type AB and (2) determine the compatibility between the blood of captive tigers and that of domestic cats with a similar blood type. The anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…On the other hand, incompatible blood crossmatches done across members of different phylogenetic groups indicate the possibility of felid group-specific erythrocyte antigens [ 63 ]. Identical results were found in Thailand [ 6 ]: when performing several crossmatch tests between tiger and domestic cat blood, the authors observed the reaction of tiger plasma with type A blood from cats, suggesting the possibility of another blood type in tigers. Recently, similar results have been found in domestic cats, where after performing 1228 crossmatches with blood from 258 type A cats, seven new naturally occurring alloantibodies outside the AB blood group system were identified [ 67 ].…”
Section: Wild Felids Ab Blood Systemsupporting
confidence: 58%
See 3 more Smart Citations
“…On the other hand, incompatible blood crossmatches done across members of different phylogenetic groups indicate the possibility of felid group-specific erythrocyte antigens [ 63 ]. Identical results were found in Thailand [ 6 ]: when performing several crossmatch tests between tiger and domestic cat blood, the authors observed the reaction of tiger plasma with type A blood from cats, suggesting the possibility of another blood type in tigers. Recently, similar results have been found in domestic cats, where after performing 1228 crossmatches with blood from 258 type A cats, seven new naturally occurring alloantibodies outside the AB blood group system were identified [ 67 ].…”
Section: Wild Felids Ab Blood Systemsupporting
confidence: 58%
“…Blood transfusions can be life-saving when required [ 5 ]. In wild felids medicine, there are common problems like run overs, parasitism, blood loss, and hypotension associated with surgical procedures, where a blood transfusion can be a life-saving procedure [ 6 , 7 ]. Reports of blood transfusions in species other than dogs and cats are very scarce in the literature, even more so in regard to wild felids [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the feline patients considered in these case reports exhibited any acute reactions after the first transfusions, leading the authors to believe that cats have no natural occurring alloantibodies against canine erythrocyte antigens (Kerr, 2002). The study from 2016 however although in both of the cases there were no initial post transfusion reactions, concluded that because of the minor crossmatch tests (Thengchaisri et al, 2017), which are positive in some cases, certain felines do have natural occurring alloantibodies against dog's RBCs.…”
Section: Summary and Discussionmentioning
confidence: 96%